Introduction to the philosophy of the human person - Ramos, Christine Carmela R. (Sampalo, Manila : Rex Book Store, Inc., 2016)
"Introduction to the Philosophy of the Human Person is given a new purpose and meaning as philosophy's response to emerging social concerns. having surveyed a broad cross section of various philosophers, from ancient to contemporary, this book presents questions and reflections to ponder in each lesson. This book hopes to achieve a substantial picture of the human being in the society. This book opposes the view of human persons as mere commodities for we have a higher calling. The calling can be divine or improving the quality of our relationships with one another, with nature and animals. Finally, this book upholds humanity's freedom and new roles vis-a-vis technological challenges."
Includes references and index.
English text.
Keywords: Philosophical anthropology; Human behavior; Philosophy -- Textbooks